2021
DOI: 10.1007/s00500-021-06095-4
|View full text |Cite
|
Sign up to set email alerts
|

New hybrid nature-based algorithm to integration support vector machine for prediction of soil cation exchange capacity

Abstract: Soil cation exchange capacity (CEC) strongly influences the chemical, physical, and biological properties of soil. As the direct measurement of the CEC is difficult, costly, and time-consuming, the indirect estimation of CEC from chemical and physical parameters has been considered as an alternative method by researchers. Accordingly, in this study, a new hybrid model using a support vector machine (SVM), coupling with particle swarm optimization (PSO), and integrated invasive weed optimization (IWO) algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Recently, hybrid machine learning models using optimization algorithms have been proposed and applied in different problems [ 47 ], Emamgholizadeh and Mohammadi [ 22 ]. This kind of hybrid models can also be built using deep learning algorithms to develop highly accurate phishing detection models in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hybrid machine learning models using optimization algorithms have been proposed and applied in different problems [ 47 ], Emamgholizadeh and Mohammadi [ 22 ]. This kind of hybrid models can also be built using deep learning algorithms to develop highly accurate phishing detection models in future work.…”
Section: Discussionmentioning
confidence: 99%
“…First, a limited initial population is randomly generated and scattered in the problemsolving space. When determining the amount of initial population and reproduction, in IWO optimization method, every member of the population produces seeds according to its capabilities [50]. The product varies linearly from the smallest possible number of seeds to the largest number, and the weeds produce more seeds with better adaptation so that the mean is zero and the standard deviation varies at different stages, ensuring that the randomly distributed seeds are very close to their parent plant.…”
Section: Invasive Weed Optimization (Iwo)mentioning
confidence: 99%
“…This approach allows the models reach to their maximum capabilities, and then the new hybrid model can have advantages of both the ANFIS and optimization algorithms for estimation [48]. Previous studies have proven that such coupled optimized techniques can provide better results in hydrological modeling [50][51][52]. Table 3 provides the optimal parameters related to the machine learning models used.…”
Section: Hybrid Models (Anfis-sfla and Anfis-iwo)mentioning
confidence: 99%
“…Emamgholizadeh and Mohammadi presented a new hybrid method based on SVM, PSO, and IWO models with SVM-PSOIWO structure for estimating soil exchange capability (CEC). Based on the findings of this paper, it can be concluded that the novel combination algorithm, when applied to the prediction of a three-month period with RMSE (R2) of 0.229 Cmol + kg −1 (0.924), has a high degree of accuracy 13 . Vadiati et al, by FL, ANFIS and SVM predicted the underground water level in the Tehran Karaj plain.…”
Section: Introductionmentioning
confidence: 83%